(untitled) (Mongolian Geoscientist, 2025)
To achieve economically efficient and safe underground coal mining, the technology of preserving and reusing workings is most effective. However, due to the effects of moisture and rheological processes, the deformation characteristics of rocks diminish. This results in actual displacements in the workings that exceed the calculated values, a factor not considered in the calculations but significant for the mines in Western Donbass. The aim of this study is to perform field measurements to identify the main patterns of deformation in the roof and floor of the workings within the influence zone of cleaning operations. The displacement calculation method for Western Donbass mines assumes a constant and uniform increase in rock contour displacements over time (except for the initial 20-40 days post-excavation), even outside the influence zone of cleaning works. The monitoring data presented here reveal the poor condition of reused workings, highlighting flaws in the calculation methodology. This study provides results from instrumental measurements and monitoring of the condition of preparatory workings during their reuse. The established patterns of deformation development in the preparatory workings allow for predicting the stability of workings supported in the worked-out part of the longwall faces in the conditions of Western Donbass mines, assessing their suitability for venting gas-air mixtures, and implementing timely technical measures to support the workings.